Relative importance of gene effects in bitter gourd (Momordica charantia L.) - Shafiullah, M; Sikdar, B (Bangladesh Journal of Botany, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Full diallel set was made in bitter gourd (Momordica charantia L.) involving six genetically divergent parents, namely BGGB1, BGGB4, BGGB6, BGGB12, BGGB13 and BGGB14 and their inheritance pattern of yield and yield contributing traits were studied. Â  Key words: Diallel cross, Gene effect, Bitter gourd DOI = 10.3329/bjb.v36i2.1512 Bangladesh J. Bot. 36(2): 189-191, 2007 (December)